PEMBERIAN LIMBAH CAIR BIOGAS DAN NPK PADA BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA - Bonar Maruli Purba; Sampurno '; M. Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research to know the effectof bioslurry fertilizer, NPK, and interaction andgetthe bestcombinationto the growthoil palm seedsinmain nursery. This research is conducted by using the Complete Random Device (CDR) consists of2 factors with 3 repetitions. The first factor is bioslurry fertilizer and the second factor is NPK. Data were analyzedusingANOVAandfollowed byfurther Different Real Honest (DRH)testat5% level. The parameters which been observed were the increment of seeds height (cm), increment of seeds leaf (sheet), increment of seeds hump diameter (cm) and root volume of seeds (ml). The results of research showed the combination of bioslurry fertilizer with NPK gived real effect to increment of seeds hump diameter (cm) and root volume of seeds (ml). 200 ml/polybag of bioslurry fertilizer with 10 g/polybag of NPK is the best combination. Giving of bioslurry fertilizer gived real effect to increment of seeds leaf (sheet) and root volume of seeds (ml). 200 ml/polybag of bioslurry fertilizer is the best bioslurry fertilizertreatment. Giving of NPK gived real effect to increment of seeds height (cm), increment of seeds leaf (sheet) and root volume of seeds (ml). 10 g/polybag of NPK is the best NPK treatment. Keywords: bioslurry fertilizer, NPK, oil palmseeds